Involvement of the AT1 receptor in the venoconstriction induced by angiotensin II in both the inferior vena cava and femoral vein - da Silva, Osmar Gomes; Rossignoli, Patrícia de Souza [UNESP]; Carrillo-Sepúlveda, Maria Alícia; Barreto-Chaves, Maria Luiza Morais; Chies, Agnaldo Bruno (Elsevier, 2011)
Although angiotensin II-induced venoconstriction has been demonstrated in the rat vena cava and femoral vein, the angiotensin II receptor subtypes (AT1 or AT2) that mediate this phenomenon have not been precisely characterized. Therefore, the present study aimed to characterize the pharmacological receptors involved in the angiotensin II-induced constriction of rat venae cavae and femoral veins, as well as the opposing effects exerted by locally produced prostanoids and NO upon induction of these vasomotorresponses. The obtained results suggest that both AT1 and AT2 angiotensin II receptors are expressed in both veins. Angiotensin II concentration–response curves were shifted toward the right by losartan but not by PD 123319 in both the vena cava and femoral vein. Moreover, it was observed that both 10−5 Mindomethacin and 10−4 M L-NAME improve the angiotensin II responses in the vena cava and femoral vein. In conclusion, in the rat vena cava and femoral vein, angiotensin II stimulates AT1 but not AT2 to induce venoconstriction, which is blunted by vasodilator prostanoids and NO.